2021 IEEE/ACM 43rd International Conference on Software Engineering (ICSE) 2021
DOI: 10.1109/icse43902.2021.00124
|View full text |Cite
|
Sign up to set email alerts
|

Why Security Defects Go Unnoticed During Code Reviews? A Case-Control Study of the Chromium OS Project

Abstract: Peer code review has been found to be effective in identifying security vulnerabilities. However, despite practicing mandatory code reviews, many Open Source Software (OSS) projects still encounter a large number of post-release security vulnerabilities, as some security defects escape those. Therefore, a project manager may wonder if there was any weakness or inconsistency during a code review that missed a security vulnerability. Answers to this question may help a manager pinpointing areas of concern and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…During the code review process, reviewers may follow the security code review practice (Howard 2006) to detect various potential security issues in the code. Prior studies have investigated the well-known security issues such as overflow, cross-site scripting, SQL injection, and cross-site request forgery that can be identified during the code review process (Paul et al 2021b;Bosu et al 2014;Bosu and Carver 2013;Edmundson et al 2013;Alfadel et al 2023;Di Biase et al 2016). Edmundson et al (2013) conducted a controlled study by asking developers to identify the injected vulnerable code in a web application called Anchor CMS.…”
Section: Code Review For Software Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…During the code review process, reviewers may follow the security code review practice (Howard 2006) to detect various potential security issues in the code. Prior studies have investigated the well-known security issues such as overflow, cross-site scripting, SQL injection, and cross-site request forgery that can be identified during the code review process (Paul et al 2021b;Bosu et al 2014;Bosu and Carver 2013;Edmundson et al 2013;Alfadel et al 2023;Di Biase et al 2016). Edmundson et al (2013) conducted a controlled study by asking developers to identify the injected vulnerable code in a web application called Anchor CMS.…”
Section: Code Review For Software Securitymentioning
confidence: 99%
“…Several studies have investigated the benefits of code reviews in identifying security issues (Alfadel et al 2023;Bosu et al 2014;Di Biase et al 2016;Edmundson et al 2013;Paul et al 2021b). Still, the security issues studied by previous works were typically bounded by the types of well-known vulnerabilities such as SQL Injection and XSS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results showed that prompting for finding security issues in code reviews significantly affects developers' identification of security issues. A study found the relevant factors in successful identification of security issues in code reviews [197]. The results indicate that the probability of security issues identification decreases with the increase in review factors such as number of reviewer's prior reviews, and number of review comments authored on a file during the current review cycle.…”
Section: Mcr Themes and Contributionsmentioning
confidence: 99%
“…CWE provides a hierarchical classification scheme for vulnerabilities [42]. To reduce the dimensionality of our analysis, we combined similar CWE categories into higher-level categories using the hierarchical structure of CWE [49].…”
Section: Data Collectionmentioning
confidence: 99%